2023
DOI: 10.1109/access.2023.3245882
|View full text |Cite
|
Sign up to set email alerts
|

D2D Assisted Multi-Antenna Coded Caching

Abstract: A device-to-device (D2D) aided multi-antenna coded caching scheme is proposed to improve the average delivery rate and reduce the downlink (DL) beamforming complexity. Novel beamforming and resource allocation schemes are proposed where local data exchange among nearby users is exploited. The transmission is split into two phases: local D2D content exchange and DL transmission. In the D2D phase, subsets of users are selected to share content with the adjacent users directly. In this regard, a low complexity D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In this section, we explain the optimal design of precoding vectors v k (n) in ( 6) to enhance the finite-SNR performance. Unlike the conventional max-min beamforming problem addressed in previous works such as [29], [32], [54], we consider a weighted-max-min (WMM) beamforming approach to enable multi-rate transmission. In this regard, we alter the iterative approach presented in [54], with a slight modification to account for the weighted beamforming requirements, wherein the weights reflect the non-uniform quantities of data transmitted to different users.…”
Section: B Weighted Max-min Beamformingmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we explain the optimal design of precoding vectors v k (n) in ( 6) to enhance the finite-SNR performance. Unlike the conventional max-min beamforming problem addressed in previous works such as [29], [32], [54], we consider a weighted-max-min (WMM) beamforming approach to enable multi-rate transmission. In this regard, we alter the iterative approach presented in [54], with a slight modification to account for the weighted beamforming requirements, wherein the weights reflect the non-uniform quantities of data transmitted to different users.…”
Section: B Weighted Max-min Beamformingmentioning
confidence: 99%
“…Later, the analysis in [29] showed that an optimized multi-antenna precoder design is necessary for the CC scheme to perform well also in the low-SNR regime. Soon, device-to-device (D2D) CC schemes were proposed (e.g., [30]- [32]) to increase the network throughput. Despite exciting theoretical gains, the real-world implementation of CC schemes has been restricted by a wide range of practical issues, which are highlighted below.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the former [41], exploiting the latter approach [42] yields more flexible and efficient communications as it does not require any overhead for network deployment. As a consequence, research on caching-based individual nodes has been showing its feasibility in a variety of contexts to enhance the system's spectrum utilization [43]- [46] and cell-edge users' performance [47]- [50] From the aforementioned discussions, it is clear that caching is a key part of future communication networks and remains relatively unexplored in conjunction with emerging technologies, such as NOMA, STAR-RIS, and SWIPT. In particular, as shown in [44], [45], exploiting caching at nearby users in coordinated NOMA systems can efficiently mitigate the impact of inter-relaying interference.…”
Section: Introductionmentioning
confidence: 99%